Transcriptomic changes throughout post-hatch development in Gallus gallus pituitary. (January 2017) - Pritchett, Elizabeth M; Lamont, Susan J; Schmidt, Carl J
Abstract : The pituitary gland is a neuroendocrine organ that works closely with the hypothalamus to affect multiple processes within the body including the stress response, metabolism, growth and immune function. Relative tissue expression (rEx) is a transcriptome analysis method that compares the genes expressed in a particular tissue to the genes expressed in all other tissues with available data. Using rEx, the aim of this study was to identify genes that are uniquely or more abundantly expressed in the pituitary when compared to all other collected chicken tissues. We applied rEx to define genes enriched in the chicken pituitaries at days 21, 22 and 42 post-hatch. rEx analysis identified 25 genes shared between all time points, 295 genes shared between days 21 and 22 and 407 genes unique to day 42. The 25 genes shared by all time points are involved in morphogenesis and general nervous tissue development. The 295 shared genes between days 21 and 22 are involved in neurogenesis and nervous system development and differentiation. The 407 unique day 42 genes are involved in pituitary development, endocrine system development and other hormonally related gene ontology terms. Overall, rEx analysis indicates a focus on nervous system/tissue development at days 21 and 22. By day 42, in addition to nervous tissue development, there is expression of genes involved in the endocrine system, possibly for maturation and preparation for reproduction. This study defines the transcriptome of the chicken pituitary gland and aids in understanding the expressed genes critical to its function and maturation.